2021
DOI: 10.21664/2238-8869.2021v10i1.p380-405
|View full text |Cite
|
Sign up to set email alerts
|

Estado da arte da geodiversidade da Amazônia legal

Abstract: A geodiversidade é uma área de estudo relativamente nova nas geociências. No Brasil a distribuição geográfica do conhecimento sobre o patrimônio natural é maior nas regiões nordeste, sudeste e sul. Esses locais possuem significativos avanços em termos de estudos, ações integradas com a comunidade e poder público e proposições de geoparques. A realidade desse background é diferente nos estados da Amazônia Legal. Esta é composta por nove estados localizados na região norte, em totalidade, um estado da região nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Only few papers have described the geodiversity in the ADB until now, including four papers that discuss geodiversity in the Amazon, namely on the 'Amazônia legal' in Brazil [37] (the northern states of Brazil, including Mato Grosso and the west of Maranhão), the Xingu river basin [38], French Guiana [35] and the NAPO Sumaco (aspiring UNESCO) Geopark [53] (figure 1). De Andrade et al [37] conducted an extensive literature study of geodiversity in the 'Amazônia legal' and concluded that there is still little known about geodiversity in this region, neither is there information on a detailed scale. The majority of the studies emphasize the geotourism potential, the importance of geoconservation and suggest the establishment of geoparks, although the terms geodiversity and geotourism were not always conceptualized or used within a methodological framework.…”
Section: (A) Previous Geodiversity Studies In the Amazon Drainage Basinmentioning
confidence: 99%
See 3 more Smart Citations
“…Only few papers have described the geodiversity in the ADB until now, including four papers that discuss geodiversity in the Amazon, namely on the 'Amazônia legal' in Brazil [37] (the northern states of Brazil, including Mato Grosso and the west of Maranhão), the Xingu river basin [38], French Guiana [35] and the NAPO Sumaco (aspiring UNESCO) Geopark [53] (figure 1). De Andrade et al [37] conducted an extensive literature study of geodiversity in the 'Amazônia legal' and concluded that there is still little known about geodiversity in this region, neither is there information on a detailed scale. The majority of the studies emphasize the geotourism potential, the importance of geoconservation and suggest the establishment of geoparks, although the terms geodiversity and geotourism were not always conceptualized or used within a methodological framework.…”
Section: (A) Previous Geodiversity Studies In the Amazon Drainage Basinmentioning
confidence: 99%
“…Only few papers have described the geodiversity in the ADB until now, including four papers that discuss geodiversity in the Amazon, namely on the ‘Amazônia legal’ in Brazil [ 37 ] (the northern states of Brazil, including Mato Grosso and the west of Maranhão), the Xingu river basin [ 38 ], French Guiana [ 35 ] and the NAPO Sumaco (aspiring UNESCO) Geopark [ 53 ] ( figure 1 ). De Andrade et al .…”
Section: Geodiversity In the Amazon Drainage Basinmentioning
confidence: 99%
See 2 more Smart Citations